Anal cancer: STATISTICAL ANALYSIS. CLINICAL FORMS. DIAGNOSIS ANDSTAGING. 90CASES. - Pittamiglio, Horacio; Matteucci, Pablo (Cirugía del Uruguay, 1983)
Ninety cases of anal cancer seen between 1960 and 1982 are reviewed. Age and sex incidence, initial symptoma tology and clinical forms are studied. ... Results and necessity of tumor and node biopsy is pointed out. Staging according U.I.C .C. andRoswell Park Memorial Foundation criteria are applied. Conclusions are taken.